Coregulation of host-adapted metabolism and virulence by pathogenic yersiniae - Heroven, Ann Kathrin; Dersch, Petra (Frontiers in Cellular and Infection Microbiology, 2014)
Deciphering the principles how pathogenic bacteria adapt their metabolism to a specific host microenvironment is critical for understanding bacterial pathogenesis. The enteric pathogenic Yersinia species Y. pseudotuberculosis and Y. enterocolitica and the causative agent of plague, Y. pestis, are able to survive in a large variety of environmental reservoirs (e.g. soil, plants, insects) as well as warm-blooded animals (e.g. rodents, pigs, humans) with a particular preference for lymphatic tissues. In order to manage rapidly changing environmental conditions and inter-bacterial competition, Yersinia senses the nutritional composition during the course of an infection by special molecular devices, integrates this information and adapts its metabolism accordingly. In addition, nutrient availability has an impact on expression of virulence genes in response to C-sources, demonstrating a tight link between the pathogenicity of yersiniae and utilization of nutrients. Recent studies revealed that global regulatory factors such as the cAMP receptor protein (Crp) and the carbon storage regulator (Csr) system are part of a large network of transcriptional and posttranscriptional control strategies adjusting metabolic changes and virulence in response to temperature, ion and nutrient availability. Gained knowledge about the specific metabolic requirements and the correlation between metabolic and virulence gene expression that enable efficient host colonization led to the identification of new potential antimicrobial targets.